Tailoring a two-dimensional graphene oxide surface: dual T1 and T2 MRI contrast agent materials1. Issue 28 (28th July 2015) - Peng, Erwin; Wang, Fenghe; Tan, Suhui; Zheng, Bingwen; Li, Sam Fong Yau; Xue, Jun Min
<x xml:space="preserve">Abstract</x> A water-soluble hybrid two-dimensional nanostructured dual T1–T2 MRI contrast agent with fair T1 and T2 nanoparticle separation distance and negligible T1/T2 signal quenching was developed.